THE EFFECT OF VARIED CONCENTRATION AND SOAKING TIME IN CORNCOB (Zea mays L) LIQUID SMOKE AT ON THE QUALITY OF SMOKED CATFISH (Pangasius pangasius) - Afrizal Riandi; Mirna Ilza; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research had been conducted in April 2015 in purpose todetermine the effect of varied concentration of corncob liquid smoke and soakingtime on the quality of smoked catfish (Pangasius pangasius). The method used inthis study was experimental, designed as Completely Randomized Design (CRD)and composed factorially 3x2. The catfish was eviscerated and then soaked in asolution of corncob liquid smoke at different concentration 4% (K4), 6% (K6) and8% (K8) for 1 hour (L1) and 2 hours (L2). After soaked, the fish were then driedusing an oven at the temperature of 55o C for 12 hours. The quality parametersused were the characteristic of organoleptic, water content, total phenols, totalacids and pH values. The results showed that the differences of concentration andsoaking time in a solution of liquid smoke affected significantly on the quality ofsmoke catfish as show on the score of the appearance, total acids and pH values,but not significantly affected on the score of the texture, odor, taste, water contentand total phenols. The best quality of smoke flavored catfish is produced bysoaking the catfish in a solution of corncob liquid smoke at concentration 6-8%for 2 hours. The characteristics of smoke flavored catfish were showing cleansurface of the meat, neat, and attractive colors (golden yellow). The smoked fishhad the specific odor of smoked fish, delicious taste and distinctive flavor ofsmoked fish, less salty, and a compact and soft texture of the meat. The smokeflavored catfish contained the water 12,88-9,14%, total phenols 0,15-0,21 ppm,total acids 3,73-5,20 and pH value 5,38-5,98.Keywords: liquid smoke, Pangasius pangasius, corncob, solution concentration,soaking time